2023
DOI: 10.3390/jpm13060922
|View full text |Cite
|
Sign up to set email alerts
|

Usage of Object Matching Algorithms Combined with Mixed Reality for Enhanced Decision Making in Orbital Reconstruction—A Technical Note

Abstract: This technical note describes the usage of object matching to virtually compare different modes of reconstruction in orbital trauma and display the results to the surgeon and the patient pre-operatively via mixed reality devices for enhanced surgical decision making and immersive patient education. A case of an orbital floor fracture is presented for which surface and volume matching were implemented to compare orbital reconstruction utilizing pre-fabricated titanium meshes versus patient-specific implants. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
(45 reference statements)
0
3
0
Order By: Relevance
“…While other methods such as head-tracked stereo glasses with 3D-like monitor-views combining haptic feedback devices have made strides in simulations of fracture repositioning in trauma cases [62], mixed reality technology takes visualization to an entirely new level. Considering the rapid advancements in mixed reality across various disciplines and the modern applications it offers, this emerging method is exceptionally promising [24,25,[63][64][65]. However, before widespread adoption, rigorous testing is required to assess its accuracy and clinical application.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While other methods such as head-tracked stereo glasses with 3D-like monitor-views combining haptic feedback devices have made strides in simulations of fracture repositioning in trauma cases [62], mixed reality technology takes visualization to an entirely new level. Considering the rapid advancements in mixed reality across various disciplines and the modern applications it offers, this emerging method is exceptionally promising [24,25,[63][64][65]. However, before widespread adoption, rigorous testing is required to assess its accuracy and clinical application.…”
Section: Discussionmentioning
confidence: 99%
“…As it is compatible with the data sets of virtual surgical planning, surgeons can already benefit from MR. During preoperative planning, MR allows the surgeons to visualize 3D models of a patient's anatomy, aiding in surgical precision and reducing surgical risks. Among other application examples for maxillofacial surgery, this technology can help with surgical decision-making concerning the preferred mode of reconstruction in orbital trauma surgery and can serve as an immersive communication platform for interdisciplinary exchange during multidisciplinary tumor boards [24,25]. Surgical training can be greatly enhanced through realistic and interactive simulations and immersive learning experiences [26,27].…”
Section: Mixed Realitymentioning
confidence: 99%
“…The study demonstrated that MR was effective in improving spatial understanding, learning, and flexibility in acupuncture practice 56 ; Wilkat et al uses Mixed Reality for a Patient Decision Aid in Orbital Repair Surgery. 57 Existing research indicates that MR technology is primarily concentrated in the fields of industrial engineering, architecture, civil engineering, surgical assistance, and medical education. Among these fields, the most research is in medical and surgical assistance equipment and systems, with a primary focus on MR development technology.…”
Section: Mixed Reality Technology To Assist In Teaching Hands-on Contentmentioning
confidence: 99%